Towards developing Islamic Equity Crowdfunding-Waqf Model (IECWM) to harness the potential of Waqf land in Malaysia - Mohd Thas Thaker, M. A.; Mohd Thas Thaker, Hassanudin * (International Islamic University Malaysia, 2019)
Over the centuries including during the era of Islamic civilization, Waqf land has played a significant role towards enhancing the social and economic status of the Muslim societies. However, in the contemporary times, Waqf land is facing the problem of underdevelopment particularly in the context of Malaysia. Currently, there are around 11,091.82 hectares of Waqf land in Malaysia that is worth about RM4 billion or equivalent to US$0.9 billion (Ali et al., 2015). Though, State Islamic Religious Councils (SIRCs) have a huge number of potential Waqf land, most of the lands are however still lying idle and remained undeveloped, mainly due to liquidity constraints or shortage of financial resources by SIRCs. Liquidity constraints have been considered as a main factor that hindered the execution of the various development plans of Waqf land in Malaysia. This thus calls for more innovative financing mechanism that can help to harness the potential of Waqf land. With this initiative, the research is developing a sustainable source of financing by integrating elements of crowdfunding and Waqf. The proposed model is known as Islamic Equity Crowdfunding-Waqf Model (IECWM). The proposed model will assist Waqf institution in identifying sustainable financing source to develop Waqf land in Malaysia. Through this, Malaysia will play a leading role among the OIC member states with the noble idea of Islamic crowdfunding and Waqf land development.